Fostering innovation in agriculture through research and development in Germany: Implications for Vietnam - Hoa Huu Cuong (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2025)
Agriculture is a crucial sector for the global economy, especially when facing challenges such as climate change and the depletion of natural resources. Fostering innovation in this sector through research and development (R&D) is one of the most effective solutions for improving productivity and sustainability in agriculture. The Federal Republic of Germany (FRG) has implemented strong R&D strategies, contributing to the development of high technology and sustainable agricultural practices. This paper analyzes Germany’s R&D policies and strategies in agriculture and draws key implications for Vietnam in fostering innovation in the agricultural sector. Code: 25021901